THE DEBATE OVER MORAL JUSTIFICATION OF STATE TERRORISM - Kartini, Indriana (Indonesia Defense University, 2014)
This essay examines the debate over moral justifications of state terrorism. Consequentialist and deontologist perspectives provide a framework to justify acts of terrorism. However, this framework can not absolutely be defended. By drawing on Tony Coady and Igor Primoratz point of views, it is argued that acts of terrorism perpetrated by the state can never be justified and it is morally wrong and worse than non-state terrorism.Â Keywords : state terrorism, moral justification, consequentialist, deontologist